Środki walki z inflacją i prognozowanie inflacji w gospodarce kapitalistycznej - Jankowiak, Ludwik (Wydział Prawa i Administracji UAM, 1982)
The article deals with the ways and means of fighting inflation in the conditions of market economy. The majority of them either reduce the aggregate demand or increase the aggregate supply. The following are being analysed. 1) appropriate monetary and fiscal policies, 2) control of wages and prices, 3) tax incentives and reductions with the aim to stabilize prices. The author concludes that the best hopes (in the long run) lie in multiaspectual approach to policies of fighting or curbing the rate of inflation, such as: a) strict adherence to fiscal and monetary discipline, b) consultations between labour, business and government, c) reductions in state expenses, d) proper regulations of business activities (with a view of expanding employment and economic growth), e) various tax reductions, f) green light for foreign trade, g) reductions in armaments expenditures, avoidance of military conflicts, h) price stabilization policies, control of cartels and monopolies. People whose responsibility is to prognosticate inflation and suggest concrete economic steps to deal with it, are in a very difficult situation. It is true that a sensible economic policy can do much in this respect — there are nonetheless different elements hard to foresee and to evaluate (the future supply-demand balance with regard to energy for one example, the price of oil etc.). Another problem which may criss-cross all expectations is the possibility of financial bankruptcy of Third World countries (and as a matter of fact, not only Third World countries). The trouble is that we lack the proper theoretical basis for making correct prognoses. In the last few years, those prognoses were mostly wrong. The econometric models used proved inefficient. New methods and instruments are needed.
The Means of Fighting Inflation — Prognostication of Inflation